2023
DOI: 10.1212/wnl.0000000000201453
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on Depressive Symptoms in Patients With Parkinson Disease

Abstract: Objective:To provide clear evidence in support of the use of exercise to improve depressive symptoms in patients with Parkinson’s disease (PD), and to investigate whether this effect differs by exercise type and intensity.Methods:Three independent reviewers searched for randomized controlled trials that applied exercise interventions with depressive symptoms as an outcome measure for patients with PD on PubMed and Web of Science up to February 28, 2022. Random effects meta-analyses were performed, in which sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…However, in a recent meta-analysis of 19 randomized controlled trials involving 1302 patients with PD, the effect size of light-to-moderate-intensity exercise was slightly higher than that of moderate-to-vigorous-intensity exercise, although both exercise intensities significantly improved depressive symptoms. 6 Similarly, a mindfulness yoga program was found to be more effective compared to stretching and resistance training exercises in reducing depressive and anxiety symptoms in patients with PD, 14 which may emphasize the importance of exercise type over intensity in improving mood symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in a recent meta-analysis of 19 randomized controlled trials involving 1302 patients with PD, the effect size of light-to-moderate-intensity exercise was slightly higher than that of moderate-to-vigorous-intensity exercise, although both exercise intensities significantly improved depressive symptoms. 6 Similarly, a mindfulness yoga program was found to be more effective compared to stretching and resistance training exercises in reducing depressive and anxiety symptoms in patients with PD, 14 which may emphasize the importance of exercise type over intensity in improving mood symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…PD was diagnosed based on the UK PD Society Brain Bank Diagnostic Criteria. Patients who met the following criteria were included: (1) aged between 50 and 80 years, (2) had a Hoehn and Yahr stage 1 or 2, (3) had the disease duration of <5 years, (4) performed less than the recommended aerobic exercise proposed by the American College of Sports Medicine (≥20 minutes of vigorous exercise ≥3 days/week or ≥30 minutes of moderate exercise ≥5 days/week), (5) were on stable dopaminergic pharmacotherapy for 3 months, (6) and had a score ≥1 in the Movement Disorder Society Unified Parkinson's Disease Rating Scale (MDS-UPDRS) part 1. We excluded patients who (1) had neurological, orthopedic, or cardiac comorbidities that made them unfit to perform aerobic exercise, (2) had a Montreal Cognitive Assessment (MoCA) score of <18, (3) were on antipsychotics, or (4) were unavailable for >10% of the study period.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several meta-analyses have confirmed that compared to control interventions, physical activity and exercise could significantly reduce depressive symptomatology in PD patients [ 85 , 89 , 90 , 91 ]. In particular, general and aerobic exercise, as well as balance training, could ameliorate depressive symptoms of PD patients while stretching exercises did not have significant antidepressant effects [ 85 ].…”
Section: Non-pharmacological Treatments For Depression In Pdmentioning
confidence: 99%
“…In particular, general and aerobic exercise, as well as balance training, could ameliorate depressive symptoms of PD patients while stretching exercises did not have significant antidepressant effects [ 85 ]. Regarding intensity, both light-to-moderate and moderate-to-vigorous exercises provided significant benefits, as shown by a recent meta-analysis [ 91 ]. Combined training interventions displayed significant effects while aerobic exercise alone did not reach a level of statistical significance in the moderator analysis of this study [ 91 ], suggesting that exercise type rather than intensity might substantially affect the antidepressant effects of physical exercise.…”
Section: Non-pharmacological Treatments For Depression In Pdmentioning
confidence: 99%